Patriotism plays an important role in the Vietnamese communist party - Nguyễn Hải Hoàng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Patriotism plays an important role, determine the existence and development of the Vietnammes Communist Party, So how is that role played? That is the basic content that the author wants to clarify in this article